6-Gingerol from Zingiberaceae as a Result of Reverse Docking for Prostateâs Cancer Potential Drug Candidate - Setyanto, Haqqi Anajili; Widiansyah, Arindra Trisna; Mustofa, Zainul (Proceeding International Conference on Global Resource Conservation, 2015)
Prostate cancer is a cancer that attacks the prostate gland causing the death rate which is high enough. One of the causes of prostate cancer is the androgen receptor (AR) in the gland cells that initiates the formation of excess cell proliferation, thus causing prostate cancer. AR inhibitor that is known is antiandrogen (biculatamide and enzalutamide). This study aimed to test the 6-gingerol compound of ginger as an AR inhibitor drug candidate for prostate cancer using silico methode. The 3D structure of the 6-gingerol compound was taken from PubChem, the prediction of targeted protein used SwissTargetPrediction and Pharmapper, analysis and docking 6-gingerol and antiandrogens with AR using Pyrx software, visualization compounds and protein interactions using PyMOLsoftware. Visualization results shows that the interaction of 6-gingerol, biculatamide, and enzalutamide with AR have the same site. This proves that the 6-gingerol is potential as anAR inhibitor candidate.Keywords: 6-gingerol; prostateâs cancer; reverse docking